El uso de cáscara de cacao en raciones para el engorde de bovinos - Bateman, J.V.; Larragan, A. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The results of a feeding trial using meal made from dried cacao pods (Theobroma cacao) as the basic ingredient for fattening yearling steers of less than 300 kg initial weight are presented. Feeding was ad libitum with rations containing 40 and 60 percent cacao pod meal. When compared with experiments in the United States using corn as the basic ration ingredient, consumption and live weight gains were surprisingly high for rations containing cacao pod meal. Animals receiving 40 percent cacao pod meal consumed dry matter at the rate of 3.4 percent of their live weight and gained an average of 1.29 Kg per day. Those receiving 60 percent cacao pod meal consumed 3.8 percent of their live weight and gained 1.14 Kg per day. Feeding efficiency was low with 9.22 Kg of dry matter required for each Kg of gain with the 40 percent cacao pod meal ration and 10.16 percent Kg for each Kg gain with the 60 percent cacao pod rations. The amount of Teobromin contained in the pod meal was not toxic, although the consumption reached 7 kg of cacao pod per day. However, a light but persistent diuretic effect was noticed at these levels of feeding.